2013
DOI: 10.1073/pnas.1219961110
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo optical trapping indicates kinesin’s stall force is reduced by dynein during intracellular transport

Abstract: Kinesin and dynein are fundamental components of intracellular transport, but their interactions when simultaneously present on cargos are unknown. We built an optical trap that can be calibrated in vivo during data acquisition for each individual cargo to measure forces in living cells. Comparing directional stall forces in vivo and in vitro, we found evidence that cytoplasmic dynein is active during minus- and plus-end directed motion, whereas kinesin is only active in the plus direction. In vivo, we found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 33 publications
4
99
0
Order By: Relevance
“…Even in the absence of an autoinhibitory tail domain, the S175D kinesin-and dynein-coated beads demonstrated a bias toward minus-end transport. A recent study indicated that dynein remains bound to the microtubule during plus-end transport, dragging behind kinesin (27). Dynein dragging acts as an opposing force on the order of a few pN that kinesin must work against.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the absence of an autoinhibitory tail domain, the S175D kinesin-and dynein-coated beads demonstrated a bias toward minus-end transport. A recent study indicated that dynein remains bound to the microtubule during plus-end transport, dragging behind kinesin (27). Dynein dragging acts as an opposing force on the order of a few pN that kinesin must work against.…”
Section: Discussionmentioning
confidence: 99%
“…Optical Trapping Assay-The optical trap setup was used as described previously with the addition of a force-feedback loop to maintain a constant load for force-velocity curve measurements (27). Motors were nonspecifically attached to carboxylated beads in a manner similar to that used in fluorescence imaging experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on the A549 cell line as prior experiments using a variety of calibration approaches had shown discrepant stall force measurement of kinesin and dynein when compared to in vitro assays 16,17 . Following the procedures in these references, we identified lipid droplets moving in opposite directions, labeling them "inward" and "outward" depending on whether they were moving from the cell periphery towards the cell nucleus or vice versa, respectively.…”
Section: Measuring Stall Forces Of Kinesin and Dynein In Vivomentioning
confidence: 99%
“…80,81 In the near future, such simulations will scale up from procaryotic to eucaryotic cells. Awaiting whole cell simulations is a new generation of experiments that look at protein folding in different organelles of the cell, 82 super-resolution structure of the cell such as the recently discovered "skeleton" of neurons 83 or time-resolved super-resolution dynamics in cell membranes, 84 in vivo characterization of motors and other cellular machinery, 85 and cryoelectron microscopy of cellular machinery. Many areas, from neurobiology to developmental biology will benefit from the development of these tools.…”
Section: Whole Cell Simulations and Experimentsmentioning
confidence: 99%